IMPROVING STUDENTS’ LISTENING ABILITY BY USING CHAIN WHISPERING WORDS OR SENTENCES TECHNIQUE AT THE FIRST YEAR OF SMP SOMBA OPU SUNGGUMINASA GOWA - Mukarrama A.; Hj. Mardianah; Abd. Muis Said (ETERNAL (English, Teaching, Learning and Research Journal), 2015)
This thesis aimed at finding out the student’s increase ability in listening by using Chain Whispering Technique and the students’ attitude toward the use of the technique. The problem statement in this research are:(1) what is the students improvement their abilities in listening by using Chain Whisper Technique? (2) What is the students’ attitude toward the use of Chain Whisper technique?. The researcher used pre experimental method with one group pre-test and post test design. The population was 60 students at the first year of SMP Somba Opu Sungguminasa Gowa in academic 2013/2014. The number of sample was 30 students. The instrument of this research consisted of two kinds’ namely listening test (pre-test and post-test) and questionnaire for students’ attitude. The mean score of the students pre-test was 6.56 and the means score of the students post-test 7.23. T-test value (6.696) was greater than T-table value (2.045). It means that chain whispering technique can increase the students’ ability listening because there is significance between pre-test and post-test increase before and after used chain whisper technique and questionnaire show that the students gave positive attitude toward. There are the importance of chain whispering technique as follow: To improve the students ability in listening skill, to measure the students ability directly in listening, to improve the students ability pronounce English word, this technique is easy to apply. (Ice Sutari, Tiem Kartini, Vismaia, (1997:143-144).